Handbook of railway vehicle dynamics - Iwnicki, S. (Simon), 1962- (Boca Raton : CRC/Taylor and Francis, 2006)
Offers an overview of major issues influencing railway vehicle dynamics. Presenting a chapter on the history of railway vehicles, this book explores the anatomy of rail vehicle suspension, railway tribology, derailment, dynamic behavior, noise, and vibration. It also covers practical issues in computer modeling, field-testing, and instrumentation.
History of railway vehicle dynamics / A.H. Wickens -- Anatomy of raileay vehicle running gear / Anna Orlova and Yuri Boronenko -- Wheel -- rail contact / Jean-Bernard Ayasse and Hugues Chollet -- Tribology of the wheel -- rail contact / Ulf Olofsson and Roger Lewis -- Track issues / Tore Dahlberg -- Gauging issues / David M. Johnson -- Railway vehicle derailment and prevention / Huimin Wu and Nicholas Wilson -- Longitudinal train dynamics / Colin Cole -- Noise and vibration from railway vehicles / David Thompson and Chris Jones -- Active suspensions / R.M. Goodall and T.X. Mei -- Simulation / Oldrich Polach, Mats Berg and Simon Iwnicki -- Field testing and instrumentation of railway vehicles / Julian Stow and Evert Andersson -- Roller rigs / Weihua Zhang ... [and others] -- Scale testing / P.D. Allen
Includes bibliographical references and index.
Keywords: Railroad cars -- Dynamics -- Handbooks, manuals, etc